Mirror neurons in the tree of life: mosaic evolution, plasticity and exaptation of sensorimotor matching responses. (16th November 2016) - Tramacere, Antonella; Pievani, Telmo; Ferrari, Pier F.
ABSTRACT: Considering the properties of mirror neurons (MNs) in terms of development and phylogeny, we offer a novel, unifying, and testable account of their evolution according to the available data and try to unify apparently discordant research, including the plasticity of MNs during development, their adaptive value and their phylogenetic relationships and continuity. We hypothesize that the MN system reflects a set of interrelated traits, each with an independent natural history due to unique selective pressures, and propose that there are at least three evolutionarily significant trends that gave raise to three subtypes: hand visuomotor, mouth visuomotor, and audio–vocal. Specifically, we put forward a mosaic evolution hypothesis, which posits that different types of MNs may have evolved at different rates within and among species. This evolutionary hypothesis represents an alternative to both adaptationist and associative models. Finally, the review offers a strong heuristic potential in predicting the circumstances under which specific variations and properties of MNs are expected. Such predictive value is critical to test new hypotheses about MN activity and its plastic changes, depending on the species, the neuroanatomical substrates, and the ecological niche.